Phosphorus and activity of acid phosphatase in common bean plants - Arnaldo Fernandes, Luiz; Eduardo Furtini Neto, Antonio; Curi, Nilton; Aparecido Aquino Guedes, Geraldo; Maria de Lima, José (Pesquisa Agropecuaria Brasileira, 1998)
The objective of this work was to evaluate the influence of the soil class, conditions of use and practices of correction of soil fertility upon dry matter production, phosphorus accumulation, phosphorus fractions and activity of acid phosphatase in vivo in common bean (Phaseolus vulgaris L.) plants. The study was conducted at greenhouse conditions of the Soil Science Department of the Universidade Federal de Lavras, Minas Gerais, Brazil, with two soils (Oxisol and Ultisol), under three conditions of use and four practices of correction of soil fertility. The highest dry matter production and P utilization efficiency was observed in plants cultivated in the Oxisol, which provided minor Pi accumulated than in the Ultisol. The activity of acid phosphatase in vivo did not reflect the nutritional state of bean plants.